2007
DOI: 10.1001/archneur.64.7.1002
|View full text |Cite
|
Sign up to set email alerts
|

Screen for Excess FMR1 Premutation Alleles Among Males With Parkinsonism

Abstract: Background: Individuals with fragile X-associated tremor/ataxia syndrome frequently have associated features of parkinsonism, often leading to an initial diagnosis of Parkinson disease or other parkinsonism spectrum disorders. Parkinson disease populations may thus include individuals who harbor premutation expansions (55-200 CGG repeats) of the fragile X mental retardation 1 (FMR1) gene. Objective: To screen DNA samples (male) from an Italian Parkinson disease clinic for an excess of premutation expansions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 29 publications
(17 reference statements)
1
30
1
Order By: Relevance
“…34 A similar study of ϳ600 adult females, using the CGG targeting method, has also been conducted (K. Amiri, J. Kraff, H.-T. Tang, R. Pan, S. Goldworm, J.P. Hagerman, F. Tassone, unpublished results), with no false-positive or negative genotypes to date. Furthermore, in the validation study performed in conjunction with Kimball Genetics, Inc., we were able to correctly identify all fifty females with full-mutation alleles (apparent homozygosity by standard PCR); this number corresponds to the expected number of full mutations in a general population of ϳ150,000 females.…”
Section: Discussionmentioning
confidence: 93%
“…34 A similar study of ϳ600 adult females, using the CGG targeting method, has also been conducted (K. Amiri, J. Kraff, H.-T. Tang, R. Pan, S. Goldworm, J.P. Hagerman, F. Tassone, unpublished results), with no false-positive or negative genotypes to date. Furthermore, in the validation study performed in conjunction with Kimball Genetics, Inc., we were able to correctly identify all fifty females with full-mutation alleles (apparent homozygosity by standard PCR); this number corresponds to the expected number of full mutations in a general population of ϳ150,000 females.…”
Section: Discussionmentioning
confidence: 93%
“…A previous study done in Indonesia reported a frequency of 8.7% for alleles with 36 CGG repeats, whereas higher frequencies were reported for alleles with 34, 35, and 36 CGG repeats in an Asian population (Zhong et al, 1994;Chiang et al, 1999;Faradz et al, 2001). A recent report showed evidence of broad clinical involvement in FMR1 gene mutations reported among premutation and gray zone alleles (Hall et al, 2006;Loesch et al, 2009) including Idiopathic Parkinson's diseases, ASD and ADHD, FXPOI, and FXTAS (Tassone et al, 2000;Jacquemont et al, 2003;Goodlin-Jones et al, 2004;Jacquemont et al, 2004;Sullivan et al, 2005;Toft et al, 2005;Kraff et al, 2007;Cilia et al, 2009). Thus, a robust screening method is needed to accommodate future directions of early intervention and anticipation.…”
mentioning
confidence: 97%
“…Although a higher prevalence of these alleles was found among males over 50 with cerebellar ataxia, OMIM# 164400 or multiple system atrophy-cerebellar type, OMIM# 146500, it was not significantly increased in small samples of males with idiopathic Parkinson disease (iPD) or parkinsonism. 1013 In a larger study of 776 patients with iPD, three carriers of the PM allele were identified, 14 which is approximately 3-fold higher than the normal population prevalence.…”
mentioning
confidence: 99%